Komunikasi Bencana: Aspek Sistem (Koordinasi, Informasi dan Kerjasama) - Setio Budi HH (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
Many catastrophic and disaster events in Indonesia provides a lesson on the importance of disaster management. Institutionally BNPB as main role and became the main command of disaster management. In reality many problems still arise in disaster management, especially “KIKK”, communication, information, coordination and cooperation. In disaster management is needed right approach that is a systems approach, in which it helps the process from mitigation to post-disaster goes well, because implemented in integrated and synergistic in inter-agency and stakeholder.